Creativity progress in the digital era - Vasić Toni; Derebey Inci; Drndar-Mujević Elifa (Univerzitetska Misao)
The progress of digitalization has been a big game changer in the fields of art and design for decades. However, the key enigma lies in the future impact of the use of digital tools on the creative process. Having determined the benefits of using digital assistance over the last years, one of the key segments that needs to be explored is the influence of the use of digital assistance on the creative process. Creative motivation on one side and technical capability on the other, this study aims to analyze the degree of influence of digital assistance in the design process. Therefore, the paper aims to identify the attributes that match the research process, particularly from the ready-made design in the field of graphic design. The benefit of non-judgmental and creative thinking has led towards creating an experiment involving second-year design students by assigning a task related to a basic design monogram project. The project consisted of three stages. The first one was oriented towards research. The second stage involved an analysis of the hand drawing of the ideas, and the last stage was elaboration of the idea with digital assistance. The students' work was categorized according to its resemblance to ready-made work of the same task found through search engines, social media, and digital design magazines. The result of this experiment is a solid foundation for understanding the level of impact digital assistance tools have on the creative process by defining the attributes shared between the students' work and the research references.